Characteristics of patients referred to a cardiovascular disease clinic for post-acute sequelae of SARS-CoV-2 infection - Stephen Y. Wang; Philip Adejumo; Claudia See; Oyere K. Onuma; Edward J. Miller; Erica S. Spatz (American Heart Journal Plus, 2022)
Introduction: There is limited literature on cardiovascular manifestations of post-acute sequelae of SARS-CoV-2 infection (PASC). Methods: This observational study aimed to describe the characteristics, diagnostic evaluations, and new cardiac diagnoses in patients referred to a cardiovascular disease clinic designed for patients with PASC, and to identify factors associated with cardiovascular symptoms with no identifiable cardiac pathology. Results: Of 126 patients, average age was 46 years, and 34 % were male. Patients presented on average five months after COVID-19 diagnosis. The most common symptoms were dyspnea (52 %), chest pain/pressure (48 %), palpitations (44 %), and fatigue (42 %), commonly associated with exertion or exercise intolerance. New cardiovascular diseases were present in 23 % of cases. The remainder exhibited common symptoms which we termed “cardiovascular PASC syndrome.” Discussion: We found that only one in four patients had a new cardiovascular diagnosis, but most displayed a pattern of symptoms associated with exercise intolerance.